Directorate General of Taxes working from home: A phenomenology of Singkawang Tax Office employees during Covid-19 pandemic - Nita Risdiana; Prahastiwi Utari; Ignatius Agung Satyawan (Universitas Negeri Yogyakarta, 2021)
Working from home (WFH) is a new thing for Directorate General of Taxes (DGT) which has the most extensive office distribution among vertical agencies of Indonesian government, surely has its own challenges in implementing WFH during Covid-19 pandemic. Such as the Singkawang Tax Office which has 86% non-homebase employees that appear to have different meaning about WFH which can affect their public service. This phenomenology study wants to examine the meaning of WFH based on the experience of DGT non- homebase employees along with their various conditions and backgrounds. Six employees were deeply interviewed by purposive sampling technique. The research findings showed that WFH was defined as new step in carrying out the government bureaucracy and public service. The different meanings of WFH were not only influenced by the location of office but also by the differences of cultural background, age, educational background, and position; that affected their performance in carrying out government bureaucracy and undergoing tasks related to public service. The reward and punishment rules for employees discipline during WFH was defined as organization’s response to maintain all organization performances. These findings raise implications for public service organizations running WFH during covid-19.